Projeto Monet: uma pesquisa-ação sobre ensino de fotografia e história da arte. - DINIZ, Valéria Santos (2024)
This dissertation explores the intersection between the pictorial and the photographic within the context of Impressionism. The central objective is to analyze the results obtained through pedagogical practices conducted with second-year high school students at the Barjonas Lobão Educational Center. The Project Monet, as it is called, proposes the replication of pictorial experiments conducted by Claude Monet and other Impressionists, albeit with a photography-based approach. In this context, students have the opportunity to familiarize themselves with the theoretical concepts of both photography and Impressionism, from the initial conception to the exhibition of their own works. This study examines the impact of this approach, exploring how the integration of photography into teaching practices can enhance the understanding of Impressionist principles and promote more meaningful learning.